Pengaruh Brand Ambassador, Brand Image, Brand Awareness terhadap Purchase Intention Produk Kecantikan Somethinc - Gebrina Ika Wahyuningtyas; Ajeng Aquinia (Peneliti.net, 2023)
Trends that are revolutionary, constantly changing create a large demand for product purchases, this also applies to the beauty product sector. Brand is not limited to brand ambassadors, brand image, or brand awareness. The selection of brand ambassadors has become a critical issue, with the hope that their presence will have a positive impact on brand image and brand awareness among consumers. Data was confirmed by the long-term attendance of over 100 people and collected through the distribution of Google Form online questionnaires to social media Twitter. Based on our research, we concluded that the variable brand ambassador has no effect on the purchase price. Furthermore, brand image and brand awareness have a positive impact on purchase intention.